3D LANDSCAPE MODELING FOR THEMATIC NONBUILDING: VEGETATION (Case Study: Campus of ITB Jatinangor) - WAHYU TRISYANTI NIM: 25115008 , SHAFARINA
A 3D City model is a digital representation of the original environment that can be used in a variety of applications, such as the planning, development, and maintenance of a city. However, 3D City models are currently more focused on building modeling. In another side, vegetation is important to model and is used in analysis by urban planners to assist urban simulations. The purpose of this research is to evaluate and develop 3D city model non-building in the form of vegetation that can be used in landscape architecture. Due to the need for analysis of landscape architecture, then made a provision of the classification, information, level of detail, and visualization of the model of vegetation objects. Data used based on survey and mapping using UAV-Photogrammetry technology. Data can be a photograph map or surface model in the form of the point cloud. Then segmentation, classification, and nDSM generation of the data to obtain information on tree position, tree crown diameter, and tree height. The information then becomes the input for modeling the 3D vegetation that follows the model template already created. The result of this research is a 3D tree model in some degree of detail that has different information based on four aspects of visualization at CityGML. 3D models created can be used for spatial analysis, especially visibility and visualization analysis in landscape architecture. Visualization of models in three levels of detail (LoD 1-LoD3) is tailored to the needs of landscape architecture. In this study, a visibility analysis was conducted to test the 3D model, which is a sun shadow analysis, which can be used by landscape architects in conducting analysis and spatial planning related to atmosphere and temperature. The analysis of sun shadow is obtained the minimum level of detail required is LoD 2.